Simulating Hydrological Responses of Integrated Crop‐Livestock Systems under Future Climate Changes in an Agricultural Watershed. (9th March 2021) - Bawa, Arun; Pérez‐Gutiérrez, Juan D.; Kumar, Sandeep
Abstract: Land use land cover (LULC) and climate are the determinant factors for the soil water balance. The combined effect of LULC and climate change is of great importance for effective water resources planning and management. This study assessed the hydrological impact of long‐term implementation of integrated crop‐livestock (ICL) system with the projected climate scenarios on water yield using the Soil and Water Assessment Tool model over two time periods (i.e., near future [2021–2050] and far future [2070–2099]). This study was conducted in three phases over Skunk Creek watershed (SCW), South Dakota. In phase I, the impact of long‐term ICL system implementation (1976–2005; 30 years) on soil hydrology was evaluated. Phase II and phase III evaluated the impacts of projected climate changes under existing land cover and ICL system, respectively. Outcomes of phase I showed a significant decrease in water yield and surface runoff. Phase II showed the susceptibility of SCW to extreme events such as floods and waterlogging during spring, and droughts during summers under the projected climate changes. Phase III showed the reduction in water yield and surface runoff due to the ICL system and minimizing the induced detrimental impacts only due to climate change. This study provides a perspective on the possible impacts of the ICL system to mitigate the hydrological alteration due to climate change. Abstract : Research Impact Statement : Future climate projections suggest noticeable hydrological alterations and Integrated Crop‐Livestock systems showed the potential to mitigate negative hydrologic impacts of climate changes.